If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 1 = 28 Reorder the terms: 1 + 3y = 28 Solving 1 + 3y = 28 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3y = 28 + -1 Combine like terms: 1 + -1 = 0 0 + 3y = 28 + -1 3y = 28 + -1 Combine like terms: 28 + -1 = 27 3y = 27 Divide each side by '3'. y = 9 Simplifying y = 9
| 5x-20=2x+4 | | 5d-2=63 | | -0.06y+0.08(1100-y)=0.36 | | 4x+3x=6x | | -3x+9=2x-6 | | 9n-12=69 | | 3y+14=5 | | -6x-17=-4x+7 | | 8(x+2)=3x+5 | | -11*3=15+-6*3 | | 7.8p-18=2.6p-5 | | 3x+8x-40=48 | | 9(x-5)=8(x-1) | | -96+5x=-8x+86 | | 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) | | 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= | | 28=(4+x)+x | | 178-5x=40x+18 | | 9-x=x | | 2(x-4)+4x=10 | | -x+-3=7 | | .75v-6=.75v-6 | | 2x2=3 | | 6(c+9)=5c-1 | | 4=0.33(b+2) | | 7(x-1)+5=6-8x+7 | | 5x+3x=7x+2 | | 9x-5=3x-59 |